2021
DOI: 10.1111/asj.13670
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of ram semen: Manual versus programmable freezing and different lengths of equilibration

Abstract: The aim of our study was to examine effects of the length of semen equilibration as well as two freezing techniques on ram sperm post‐thaw quality. The ejaculates of Wallachian sheep rams (n = 12) were collected by an electro‐ejaculation, equilibrated in a Triladyl® (0, 2, 4, 6, and 8 h) containing glycerol and egg yolk and frozen by programmable freezing (PF) or manual freezing (MF). After thawing, sperm samples were subjected to the motility (computer‐assisted sperm analysis [CASA]), viability (SYBR‐14/PI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…Rams were kept under external conditions in individual stalls at a breeding facility (NPPC, RIAP Nitra, Lužianky, Slovak Republic) and fed with hay bales and oats; water and mineral salts were supplied ad libitum. Semen samples ( n = 58) were collected twice a week by electro-ejaculation and immediately transported to the laboratory throughout the whole study (September–November), as described previously [ 82 ]. The study was conducted during the breeding season because it was reported that seasonality can influence ram reproductive organs [ 83 ] and reproductive performance in general.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rams were kept under external conditions in individual stalls at a breeding facility (NPPC, RIAP Nitra, Lužianky, Slovak Republic) and fed with hay bales and oats; water and mineral salts were supplied ad libitum. Semen samples ( n = 58) were collected twice a week by electro-ejaculation and immediately transported to the laboratory throughout the whole study (September–November), as described previously [ 82 ]. The study was conducted during the breeding season because it was reported that seasonality can influence ram reproductive organs [ 83 ] and reproductive performance in general.…”
Section: Methodsmentioning
confidence: 99%
“…Sperm motility and concentration were assessed using CASA system with Sperm Vision™ software (MiniTube, Tiefenbach, Germany) as described previously [ 82 ]. Briefly, each fresh semen sample was analyzed for average concentration (10 9 spermatozoa/mL, percentage of totally motile spermatozoa (motility > 5 μm/s) and percentage of progressively motile spermatozoa (motility > 20 μm/s).…”
Section: Methodsmentioning
confidence: 99%
“…Although the spermatozoa motility will decrease after thawing, it can theoretically be preserved permanently. However, ram spermatozoa is very sensitive to freezing compared to other species because of spermatozoa membrane containing too much polyunsaturated fatty acids (PUFAs) 9 , 10 . Therefore, in order to minimize the impact of freezing shock, it is essential to establish an appropriate freezing protocol for ram semen.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the stabilization of sperm with an adequate cooling rate coupled with a suitable adaptation period to the extender would enable them to overcome the damaging effects of the different stress factors to which they are subjected in semen preservation [ 19 ]. There are many studies on the impact of this adaptation time on the cryoresistance of sperm from several species, such as dogs [ 20 , 21 ], boars [ 22 , 23 , 24 ], bulls [ 25 , 26 , 27 , 28 ], bucks [ 29 ], and rams [ 30 , 31 , 32 , 33 , 34 ], with different outcomes. For ram sperm, in general, an adaptation period of 2 to 8 h seems to be sufficient to ensure greater post-thawing sperm quality [ 35 , 36 ], but we have also noticed that the adaptation time to the extender during liquid storage influences sample quality.…”
Section: Introductionmentioning
confidence: 99%